Approaches to Antarctic solid waste management logistics : past, present, potential - Potter, S (2003)
Past and present solid waste management practices in Antarctica, and the local impacts of waste, are described. The provisions of Annex III of the Protocol on Environmental Protection to the Antarctic Treaty (the Madrid Protocol) are reviewed, in particular the requirement to remove waste from Antarctica and clean up past waste disposal sites and abandoned infrastructure. It is noted that the language used in the Protocol, and the absence of clearly defined environmental standards for the region, make examination of the compliance of signatories problematic. Australian, French, Russian, Chinese and Japanese program policy and operations in East Antarctica are discussed. Issues related to the on-site processing, containment and shipment of waste are considered in an Integrated Solid Waste Management System framework. Particular reference is made to the differing demands presented by the erection and demolition of facilities, the handling of annually generated and principally non-hazardous domestic waste, and the clean up of abandoned, and often contaminated, sites. A lack of sufficiently-detailed, reliable and consistently-described data on the composition and production of waste, the volumes accumulated, and the effects and efficiency of Antarctic operations, currently hinders strategic planning. Nevertheless it is suggested that a collaborative approach to the removal of waste from coastal sites between 30°E (Syowa station) and 140°E (Dumont d'Urville) is logistically feasible and attractive on environmental, practical and economic grounds. Australia is appropriately positioned, geographically and in the Antarctic Treaty System (ATS), to take a lead role in promoting and implementing a coordinated, regional approach. Concomitantly it is argued that ATCPs need to give greater attention to philosophical and theoretical issues related to operating in Antarctica, the debate involving enquiry beyond that associated with scientific objectivity and analysis. Similarly, establishing the means by which the participation of stakeholders outside the ATS can be enhanced, requires urgent consideration.